2021
DOI: 10.18231/j.ijn.2021.041
|View full text |Cite
|
Sign up to set email alerts
|

An advance of complex multifaceted root learning for parkinson behavior using subthalamic nucleus biomarkers

Abstract: Though DBS is suiting well to Parkinson`s still its current version being modified now and often as suggested by the neuroscientists. The technique has gained an effectual management surgical therapy concerned to PD, explicitly whilst growing idea as an effectual method to alleviate Parkinson’s disease and other movement disorders. The present ver.1 indirect DBS is an open loop based and its parameters are changeable manually and there is no provision to adjust automatically or online based on Parkinson diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…25 In our NW we prove that probing the, investigating -studying the brain's 'problem-solving' capabilities flanking, combining with its aim of spending as limited resources equally feasible and capable of aid us recognize why, wherefore and wherefor brains act and looklike, look as if they accomplish and then fix. [26][27][28][29][30][31][32][33][34] In other studies [35][36][37][38][39][40][41][42][43][44] Co-lead author Dr. Danyal Akarca, as well as of from the MRC CBSU, supplemented, this originates as of an extensive source, that is the biologic-systems frequently acquire to generate the maximum and majority of what kind of active/energetic properties/resources that they have obtainable for them. The explanations and resolutions they arise to are frequently and repeatedly extremely neat and sophisticated also signal the business/trade-offs connecting numerous several forces impressed over on them.…”
Section: Introductionmentioning
confidence: 99%
“…25 In our NW we prove that probing the, investigating -studying the brain's 'problem-solving' capabilities flanking, combining with its aim of spending as limited resources equally feasible and capable of aid us recognize why, wherefore and wherefor brains act and looklike, look as if they accomplish and then fix. [26][27][28][29][30][31][32][33][34] In other studies [35][36][37][38][39][40][41][42][43][44] Co-lead author Dr. Danyal Akarca, as well as of from the MRC CBSU, supplemented, this originates as of an extensive source, that is the biologic-systems frequently acquire to generate the maximum and majority of what kind of active/energetic properties/resources that they have obtainable for them. The explanations and resolutions they arise to are frequently and repeatedly extremely neat and sophisticated also signal the business/trade-offs connecting numerous several forces impressed over on them.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 But prognostics and computational observations have shown that the success of STN-DBS varies profoundly in setting the DBS electrodes through superior accuracy obsessed by the sensori-motor zone of s-nuclei corresponding to the dorso lateral base portion-of-nucleus. [5][6][7][8][9] The somatotopic scenario of sensorimotor zone in STN plus it is relative to movement and tremor in Parkinson subjects has been highly instituted. 10,11 MER gives the correction position of the STN and based on MER signal patterns (signatures), the STN is identified and implanted DBS electrodes.…”
Section: Introductionmentioning
confidence: 99%